2014
DOI: 10.1016/j.joca.2014.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the therapeutic effect of treatment with intra-articular hyaluronic acid in knees for Kashin-Beck disease: A meta-analysis

Abstract: IAHA for the treatment of KBD was safe and efficacious at 12 months with low and transient adverse reactions. However, more high-quality randomized controlled trials (RCTs) are needed to confirm its therapeutic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
(11 reference statements)
0
13
0
Order By: Relevance
“…Thus, the increasing recognition of environmental risk factors for the development of clinical KBD and the advent of highly sensitive imaging modalities for visualizing cartilage damage, as well as early synovitis may greatly enhance the appreciation of early anti-inflammatory interventions. Current therapies, such as selenium, intra-articular hyaluronic acid injections, nonsteroidal anti-inflammatory drugs (NSAID), COX-2 selective agents, vitamins and chondroitin sulfate showed efficiency for relieving discomfort of KBD patients [11][12][13][14][15][16][17][18]. Although several studies have demonstrated that the efficacy of meloxicam [13,49], a COX-2-specific inhibitor, is effective in the treatment of knee pain due to KBD, no agent has been shown to have disease modifying effects on the structural progression of KBD.…”
Section: Inflammation As a Target For Treatment Of Kbdmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the increasing recognition of environmental risk factors for the development of clinical KBD and the advent of highly sensitive imaging modalities for visualizing cartilage damage, as well as early synovitis may greatly enhance the appreciation of early anti-inflammatory interventions. Current therapies, such as selenium, intra-articular hyaluronic acid injections, nonsteroidal anti-inflammatory drugs (NSAID), COX-2 selective agents, vitamins and chondroitin sulfate showed efficiency for relieving discomfort of KBD patients [11][12][13][14][15][16][17][18]. Although several studies have demonstrated that the efficacy of meloxicam [13,49], a COX-2-specific inhibitor, is effective in the treatment of knee pain due to KBD, no agent has been shown to have disease modifying effects on the structural progression of KBD.…”
Section: Inflammation As a Target For Treatment Of Kbdmentioning
confidence: 99%
“…For the prevention or treatment of KBD, sodium selenite [11,12], pain killers and anti-inflammatory drugs [13], vitamins [14], hyaluronic acid [15], chondroitin sulfate and glucosamine [16] have been used. Thanks to these measures, KBD in children is under control and has almost disappeared today.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21]. Studies focusing on treatment evaluation have shown that medication, physical therapy, and surgery can help to alleviate symptoms, delay cartilage degeneration, and improve joint function [6][7][8][9][10][11][12]. In addition, results from 2520 children and adults with KBD (ages, 1-60 years) using single-factor logistic regression modeling showed that, along with increased age and prolonged disease, the major indicators of KBD were joint pain, morning stiffness, joint dysfunction (wrist, elbow, ankle, knee, and shoulder), finger coarse, bone end, knee deformity, and scoliosis [22].…”
Section: Feasibility Analysismentioning
confidence: 99%
“…The WOMAC score was employed to compare the efficacy of celecoxib, meloxicam, and paracetamol in elderly subjects with KBD [11]. Collectively, the Lysholm score, WOMAC score, Lequence score, VAS score, HSS score, functional score, and SF-12 represent different application of the osteoarthritis scale [12].…”
Section: Introductionmentioning
confidence: 99%
“…Both HA and HA binding protein (HABP) are important components of articular cartilage whose damage is the principal pathologic feature of KBD [18]. Intra-articular hyaluronic acid (IAHA) injection has been used to treat patients with KBD [19]. Therefore, we also investigated the potential association between KBD susceptibility and variants in COL10A1 and HABP2 genes by directly sequencing the exons of both genes.…”
Section: Introductionmentioning
confidence: 99%